Simultaneous determination of twelve mycotoxins in edible oil, soy sauce and bean sauce by PRiME HLB solid phase extraction combined with HPLC-Orbitrap HRMS - Luo, Donghui; Guan, Jingjing; Dong, Hao; Chen, Jin; Liang, Ming; Zhou, Chunxia; Xian, Yanping; Xu, Xiaofei (Frontiers in Nutrition, 2022)
A solid phase extraction-high-performance liquid chromatography-tandem Orbitrap high resolution mass spectrometry (HPLC-Orbitrap HRMS) method was established for the determination of 12 mycotoxins (ochratoxin A, ochratoxin B, aflatoxin B1, aflatoxin B2, aflatoxin G1, aflatoxin G2, HT-2 toxin, sterigmatocystin, diacetoxysciroenol, penicillic acid, mycophenolic acid, and citreoviridin) in edible oil, soy sauce, and bean sauce. Samples were extracted by 80:20 (v:v) acetonitrile-water solution, purified by PRiME HLB column, separated by aQ C18 column with mobile phase consisting of 0.5 mmol/L ammonium acetate-0.1% formic acid aqueous solution and methanol. The results showed that the limits of detection (LODs) and limits of quantification (LOQs) of 12 mycotoxins were 0.12-1.2 μg/L and 0.40-4.0 μg/L, respectively. The determination coefficients of 12 mycotoxins in the range of 0.20-100 μg/L were > 0.998. The average recoveries in soy sauce and bean sauce were 78.4-106.8%, and the relative standard deviations (RSDs) were 1.2-9.7% under three levels, including LOQ, 2× LOQ and 10× LOQ. The average recoveries in edible oil were 78.3-115.6%, and the precision RSD (n=6) was 0.9-8.6%. A total of 24 edible oils, soy sauce and bean sauce samples were analyzed by this method. AFB1, AFB2, sterigmatocystin and mycophenolic acid were detected in several samples at concentrations ranging from 1.0 to 22.1 μg/kg. The method is simple, sensitive, and rapid and can be used for screening and quantitative analysis of mycotoxin contamination in edible oil, soy sauce, and bean sauce.